The Effect of Using Eugenol Essential Oil of Clove Leaf as a Feed Additive on The Carcass Percentage and Carcass Components of Broiler Chickens - Tahir, Muhammad; Hafsah, Hafsah; Widodo, Eko (Faculty of Agriculture, 2024)
Eugenol, derived from clove leaf essential oil, possesses antibiotic, antifungal, anti-inflammatory, and antioxidant properties. This study aimed to evaluate the effects of eugenol as a feed additive on carcass percentage and carcass components in broiler chickens. A Completely Randomized Design (CRD) was used, with four treatments and five replications. Two hundred 1-week-old chicks with an average initial body weight of 142.257.75 g were allocated into 20 cage plots. The treatments were: E0 (Basal ration), E1 (Basal ration + 0.5% eugenol), E2 (Basal ration + 1.0% eugenol), and E3 (Basal ration + 1.5% eugenol). Carcass percentage and carcass component percentages were measured. Analysis of variance revealed a highly significant effect (P0.01) on carcass percentage and upper thigh percentage; a significant effect (P0.05) on the percentage of breast, wings, and back; and no significant effect (P0.05) on the percentage of the lower thigh. The 1% eugenol treatment achieved the highest carcass percentage (77.751.04%), breast percentage (39.020.61%), and upper thigh percentage (17.800.09%) compared to other treatments.